High-Fat Diet Induced Gut Microbiota Alterations Associating With Ghrelin/Jak2/Stat3 Up-Regulation to Promote Benign Prostatic Hyperplasia Development - Gu, Meng; Liu, Chong; Yang, TianYe; Zhan, Ming; Cai, Zhikang; Chen, Yanbo; Chen, Qi; Wang, Zhong (Frontiers in Cell and Developmental Biology, 2021)
The role of high-fat diet (HFD) induced gut microbiota alteration and Ghrelin as well as their correlation in benign prostatic hyperplasia (BPH) were explored in our study. The gut microbiota was analyzed by 16srRNA sequencing. Ghrelin levels in serum, along with Ghrelin and Ghrelin receptor in prostate tissue of mice and patients with BPH were measured. The effect of Ghrelin on cell proliferation, apoptosis, and induction of BPH in mice was explored. Our results indicated that BPH mice have the highest ratio of Firmicutes and Bacteroidetes induced by HFD, as well as Ghrelin level in serum and prostate tissue was significantly increased compared with control. Elevated Ghrelin content in the serum and prostate tissue of BPH patients was also observed. Ghrelin promotes cell proliferation while inhibiting cell apoptosis of prostate cells. The effect of Ghrelin on enlargement of the prostate was found almost equivalent to that of testosterone propionate(TP) which may be attenuated by Ghrelin receptor antagonist YIL-781. Ghrelin could up-regulate Jak2/pJak2/Stat3/pStat3 expression in vitro and in vivo. Our results suggested that Gut microbiota may associate with Ghrelin which plays an important role in activation of Jak2/Stat3 in BPH development. Gut microbiota &Ghrelin might be pathogenic factors for BPH and could be used as a target for mediation.